Analisis Kandungan Merkuri (Hg) pada Badan Air, Sedimen dan Biota yang Terdampak Aktivitas Pertambangan Emas di Kabupaten Parigi Moutong: Analysis of Mercury (Hg) Content in Water Bodies, Sediments, and Biota Affected by Gold Mining Activities in Parigi Moutong District - Ernawaty Rasul; Musafira Musafira (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2022)
Parigi Moutong District is one of the regencies in Central Sulawesi province with the highest number of illegal mining activities. Unlicensed mining activities generally use mercury as an extracting agent and gold processing waste is generally disposed of in rivers or other water bodies. The purpose of this study was to analyze the levels of heavy metal mercury (Hg) in water bodies, sediments, and marine biota in gold mining areas in Parigi Moutong District. The sampling method was carried out by random sampling method, while the analysis of mercury content in samples of river water, sediment, and biota was carried out using atomic absorption spectroscopy (AAS). From the results of the study, it was found that mercury levels in water and sediment samples were still below the quality standard value which were 0.001 mg/Kg and 0.13 mg/Kg, respectively, while the mercury levels in all biota samples had exceeded the quality standard values ​(0.03 mg/Kg). This indicates that mercury has accumulated in the food chain in the water near the mine site.